PENGEMBANGAN MEDIA KOMIK DALAM PEMBELAJARAN BAHASA INDONESIA TEMA CITA-CITAKU DI MI HIDAYATUN NAJAH TUBAN - Lailatul I’zaati; Akhmad Aji Pradana; Rr. Kusuma Dwi Nur Ma'rifati (PREMIERE : Journal of Islamic Elementary Education, 2022)
This research was motivated by researchers who had conducted pre-research at MI Hidayatun Najah Tuban, in the process of implementing Indonesian language learning activities, they were still driven by Yudistira's book and local books devoted to learning MI Hidayatun Najah Tuban. The educators stated that teachers tend to focus more on books and have not used a variety of learning media on the theme of my ideals. From the methods and learning media used by teachers in the learning process, problems arise when teachers test students' understanding with questions and answers conducted by teachers to students. In fact, in learning Indonesian, they have completed and understand the material on ideals and material about poetry. The formulation of the problem in this research is how the validity, practicality and effectiveness of comics media in learning Indonesian with the theme of Cita-citaku class III E at MI Hidayatun Najah Tuban. This study uses the Research and Development (R&D) method which takes the 4-D development model. The 4-D development model goes through 4 stages, namely defining or defining, planning or designing, developing or developing, and disseminating or disseminating. However, the researcher limits the research stage to only the development stage. The research subject is in class III MI Hidayatun Najah Tuban. Based on the results of research that has been carried out by researchers, the results show that the validity test with a score of two validators, namely material expert validators 96% and media expert validators 87% with an average validation result of 91.5% with a very valid / very feasible category through the results the percentage of feasibility so that the Indonesian language learning comic media is feasible to use. The results of the practicality test from the results of the observation sheet on the implementation of learning obtained based on observations of the learning that have been carried out obtained a total score of 10 aspects with a percentage of 91% in the very good category. The results of student questionnaires obtained 90%, namely students who are interested in Indonesian language learning comics media can improve students' understanding. The results of the teacher's questionnaire were 83%, namely that comic media could improve students' understanding in the Good category. So that Indonesian comics are practically used for the learning process. The effectiveness of comics media is seen from the increase in student learning outcomes in the high category according to the gain score category with a total of 19 in the high category. From this development, it can be concluded that the Indonesian Language Learning Comic Media is categorized as very valid, practical, and effectively used in learning Indonesian to improve the understanding of third grade students of MI Hidayatun Najah Tuban.